Computer aided instruction of load flow analysis in the undergraduate power engineering classes at Monash University - Zahedi, A.; Voumard, P.R. (1995 IEEE International Conference on Systems, Man and Cybernetics, 1995)
The subject of power system analysis and design is one of the major undergraduate components in electrical engineering courses. Computer applications in this subject yield significant insight into a complete electric power system. To help students to better understand the subject, a computerised program has been developed to illustrate the analytical procedure of power system. The program is used for teaching the subject from an analysis and design point of view as well as for explaining the structure and operation of the system. In the program, the analytical characteristics of the major parts of the power system are described. The program developed to teach the fundamentals of power system and to show the analytical procedures used.